Key norisoprenoid compounds in wines from early-harvested grapes in view of climate change. (1st December 2018) - Asproudi, Andriani; Ferrandino, Alessandra; Bonello, Federica; Vaudano, Enrico; Pollon, Matteo; Petrozziello, Maurizio
Highlights: The link between seasonal trend, grape ripening and wine aroma, was assessed. Barbera and Pinot Noir wines from early harvested grapes were produced. Norisoprenoids were quantified in wines during fermentation and after three months. The highest β-damascenone content was detected in wines from less mature grapes. β-Damascenone content increased during wine shelf life. Abstract: In view of climate change, the scheduling of an early harvest may be an agronomic option to limit wine alcohol, provided that a satisfactory content of secondary metabolites can be ensured in grapes. To better understand the link between grape ripening, seasonal trend and wine aroma, the aromatic expression of Barbera and Pinot Noir wines produced with early harvested grapes was assessed. Attention was focused on C13 norisoprenoids during both alcoholic fermentation and after three months of storage. At the end of fermentation, the highest β-damascenone content was detected in wines obtained from less ripe grapes, the content subsequently increased significantly after three months of storage; however, the levels of β-ionone decreased significantly during the same period. The reduction of wine alcohol as a result of harvesting earlier, especially for Barbera, was associated with optimal aromatic levels as well as good technological parameters.